Fenomena Fomo Sapiens : Kematian Identitas sebagai Homo Sapiens - Wahyu Trisno Aji; Rosiana Sri Wulandari (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This article will discuss a social phenomenon known as FOMO Sapiens, which is a depiction of modern humans who live in a paradox between high awareness of world developments and the inability to understand the essence and existence of themselves. They are trapped in excessive fear and stress when they feel left behind by trends, innovations, or updates, so that their lives are filled with the need for validation and recognition from the social environment. Ironically, even though they continue to seek connection and existence in cyberspace, they are increasingly distant from authentic connections with themselves and the real environment around them. This phenomenon shows human alienation from the true purpose of their lives, where their focus is more on quantity, how many things they can achieve or show off than on quality, which is the true meaning of what they do. In this article, several case analyses of FOMO Sapiens are presented as an easy way to understand it. In a clearer understanding, FOMO Sapiens depicts humans who "worship" the material world and ephemerality more, forgetting the true existence that should prioritize introspection, creativity, and deep meaning of life.